Effect of molecular intercalation on the local structure of superconducting Nax(NH3)yMoSe2 system. (December 2017) - Simonelli, L.; Paris, E.; Wakita, T.; Marini, C.; Terashima, K.; Miao, X.; Olszewski, W.; Ramanan, N.; Heinis, D.; Kubozono, Y.; Yokoya, T.; Saini, N.L.
Abstract: We have studied the local structure of layered Na x (NH3 ) y MoSe2 system by Mo K-edge extended X-ray absorption fine structure (EXAFS) measurements performed as a function of temperature. We find that molecular intercalation in MoSe2 largely affects the Mo-Se network while Mo-Mo seems to sustain small changes. The Einstein temperature ( Θ E ) of Mo-Mo distance hardly changes ( ∼ 264 K) indicating that bond strength of this distance remains unaffected by intercalation. On the other hand, Mo-Se distance suffers a softening, revealed by the decrease of Θ E from ∼ 364 K to ∼ 350 K. The results indicate that Na + ion transported by NH3 molecules may enter between the two MoSe-layers resulting reduced Se-Se coupling. Therefore, increased hybridization between Se 4p and Mo 4d orbitals due to inter-layer disorder is the likely reason of metallicity in intercalated MoSe2 and superconductivity at low temperature. Highlights: The effect of molecular intercalation on the local structure of MoSe2 has been studied. Molecular intercalation largely affects the Mo-Se network while Mo-Mo seems to sustain small changes. The Einstein temperature of Mo-Mo distance hardly changes, indicating Mo-Mo bond strength remains unaffected. Intercalation of Na + -ion between the MoSe-layers seems to reduce the Se-Se coupling. The increased hybridization of Se and Mo orbitals due to inter-layer disorder appears important for intercalated MoSe2 .